El derecho a la propiedad privada consagrado en la constitución de la república del ecuador y su vulneración mediante la declaratoria de utilidad pública con fines de expropiación - Robles Miranda, Byron Patricio (2017)
In the work done; an analysis of the legal rules established in the Constitution of the Republic of Ecuador, the Civil Code, the Ecuadorian Civil Procedure and other laws such as COOTAD and organic law of the national public procurement system, dealing in relation is comprised the declaration of public utility for purposes of expropriation under Ecuadorian law; which is why the development of this research has been analyzed everything has to do with private property and expropriation: its history, constitutional development, the requirements for their existence and all that encompasses the subject to be treated The theme chosen for this thesis states: "The right to property embodied in the Constitution of THE REPUBLIC OF ECUADOR AND THEIR INFRINGEMENT BY declaration of public utility in order to expropriate"; Same were raised aimed perform, conceptual, doctrinal, and legal study on the right to private property and the declaration of public utility for purposes of expropriation in Ecuador Similarly, the hypothesis states: "The declaration of public utility for purposes of expropriation violates the right to private property enshrined in the Constitution of the Republic of Ecuador". To get to check each of these expressions, I did a literature search that was the basis for the field research itself on the opinion of legal professionals who obtained it was established conclusion that the declaration of public utility is a unilateral administrative act which infringes the right of the expropriated causing serious damage socially and economically. It is understood, therefore, that research framed in a deep doctrinal legal analysis has validity and reliability criteria that professional lawyers with vast experience provided me, to finally present the conclusions, recommendations and legal reform as an alternative solution to this problem.